Cellular transcriptomics of arrested normal lung fibroblasts IMR-90 infected with Human Adenovirus 5 E1A mutants - Rafe Helwer; Peter Pelka (PLoS ONE, 2025)
Induction of S-phase is paramount to the replication of most human DNA viruses. Human adenoviruses have evolved sophisticated mechanisms that drive the infected cells into S-phase to ensure that viral genomes are efficiently replicated. We have identified an E1A mutant, E1A289Rdl2–11/YC, that disrupts the canonical means of S-phase induction by E1A. Specifically, this mutant abrogates binding of E1A to the E2F/DP complex as well as to the retinoblastoma protein. Yet, we show that this mutant can still effectively drive the infected cell into S-phase. We explore potential mechanisms of how this occurs via cellular transcriptomic analysis 16 hours after infection. We show that this mutant induces many cell-cycle specific genes to drive S-phase. Interestingly, MYC mRNA is significantly upregulated by this mutant as compared to other viruses investigated. This MYC upregulation, together with normal expression of E4orf6/7 in this mutant, may contribute to efficient S-phase induction. We also demonstrate that this mutant is unable to effectively suppress innate immune response to infection, likely due to loss of p300/CBP binding caused by deletion of E1A residues 2 to 11.